Resonant energy transfer and light scattering enhancement of plasmonic random lasers embedded with silver nanoplates. Issue 13 (19th February 2020) - Hsiao, Jia-Huei; Chen, Shih-Wen; Hung, Bing-Yi; Uma, Kasimayan; Chen, Wei-Cheng; Kuo, Chi-Ching; Lin, Ja-Hon
Abstract : The resonant energy transfer enhancement from a plasmonic random laser has been investigated by means of a dye-covered PVA film embedded with silver nanoplates with different sizes and morphologies. Abstract : The resonant energy transfer enhancement from a plasmonic random laser (PRL) has been investigated by means of a dye-covered PVA film with embedded silver nanoplates (DC-PVA/AgNPs). Different sizes and morphologies of AgNPs were adopted to shift the localized surface plasmon resonance (LSPR) and intensify recurrent light scattering between the AgNPs. For better overlap between surface plasmon resonance and the photoluminescence of fluorescent molecules with appropriately-sized silver nanoprisms, the slope efficiency of the PRL was greatly enhanced and the lasing threshold was obviously reduced. In addition, the photon lifetime for the DC-PVA/AgNPs film reveals an apparent decline around 1.39 ns owing to better coupling with LSPR. The stronger light scattering of samples with bigger-sized silver nanoprisms has been demonstrated by coherent back scattering measurements, which reveals a smaller transport mean free path around 3.3 μm. With α -stable analysis, it has been successfully demonstrated that the tail exponent α can be regarded as an identifier of the threshold of random lasing.